Au Sub‐Nanoclusters on TiO2 toward Highly Efficient and Selective Electrocatalyst for N2 Conversion to NH3 at Ambient Conditions. Issue 17 (27th February 2017) - Shi, Miao‐Miao; Bao, Di; Wulan, Ba‐Ri; Li, Yong‐He; Zhang, Yue‐Fei; Yan, Jun‐Min; Jiang, Qing
Abstract : As the NN bond in N2 is one of the strongest bonds in chemistry, the fixation of N2 to ammonia is a kinetically complex and energetically challenging reaction and, up to now, its synthesis is still heavily relying on energy and capital intensive Haber–Bosch process (150–350 atm, 350–550 °C), wherein the input of H2 and energy are largely derived from fossil fuels and thus result in large amount of CO2 emission. In this paper, it is demonstrated that by using Au sub‐nanoclusters (≈0.5 nm ) embedded on TiO2 (Au loading is 1.542 wt%), the electrocatalytic N2 reduction reaction (NRR) is indeed possible at ambient condition. Unexpectedly, NRR with very high and stable production yield (NH3 : 21.4 µg h −1 mg −1 cat., Faradaic efficiency: 8.11%) and good selectivity is achieved at −0.2 V versus RHE, which is much higher than that of the best results for N2 fixation under ambient conditions, and even comparable to the yield and activation energy under high temperatures and/or pressures. As isolated precious metal active centers dispersed onto oxide supports provide a well‐defined system, the special structure of atomic Au cluster would promote other important reactions besides NRR for water splitting, fuel cells, and other electrochemical devices. Abstract : Using Au sub‐nanoclusters anchored on TiO2 substrate as a heterogeneous electrocatalyst, the special Au active sites lead to the effective and stable electrochemical N2 reduction reaction with high NH3 yield (21.4 µg h −1 mg −1 cat. ) and Faradaic efficiency (8.11%) as well as 100% NH3 selectivity at ambient conditions.